2014
DOI: 10.1371/journal.pone.0115388
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Emotions Predict Food Choice

Abstract: In the current study we show that non-verbal food-evoked emotion scores significantly improve food choice prediction over merely liking scores. Previous research has shown that liking measures correlate with choice. However, liking is no strong predictor for food choice in real life environments. Therefore, the focus within recent studies shifted towards using emotion-profiling methods that successfully can discriminate between products that are equally liked. However, it is unclear how well scores from emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 29 publications
3
103
0
1
Order By: Relevance
“…In various laboratory (Garcia-Bailo, Toguri, Eny, & El-Sohemy, 2009;Hasselbalch, Heitmann, Kyvik, & Sorensen, 2008) and real life studies (De Graaf et al, 2005), liking ratings have been shown to relate to food choice and food intake. In a recent study (Dalenberg et al, 2014) we demonstrated that food-evoked emotions better predict food choice than liking scores alone. However, combining emotion scores with liking ratings resulted in the best prediction of choice for tasted products without packaging information.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In various laboratory (Garcia-Bailo, Toguri, Eny, & El-Sohemy, 2009;Hasselbalch, Heitmann, Kyvik, & Sorensen, 2008) and real life studies (De Graaf et al, 2005), liking ratings have been shown to relate to food choice and food intake. In a recent study (Dalenberg et al, 2014) we demonstrated that food-evoked emotions better predict food choice than liking scores alone. However, combining emotion scores with liking ratings resulted in the best prediction of choice for tasted products without packaging information.…”
Section: Introductionmentioning
confidence: 89%
“…A detailed description of this approach can be found in Dalenberg et al (2014). In short, two Principal Component Analyses (PCAs) were performed on the emotion scores of all participant-product combinations for the blind taste choice context (B) and the package choice context (P), separately.…”
Section: Analysis On the Effect Of Liking And Food Emotions On Choicementioning
confidence: 99%
“…Siegrist (2008) established that psychological factors influence the acceptance of foods. Likewise Lockie et al (2004), , Dalenberg et al (2014), Barrena et al (2015) and Gutjar et al (2015) concluded that there is a considerable emotional dimension associated with the purchase and consumption of a new food. Nevertheless, found that emotional intensity is sometimes related to acceptance and sometimes differs, suggesting that food acceptance does not depend solely on emotions.…”
Section: Introductionmentioning
confidence: 99%
“…The current results can provide R&D guidance beyond the traditional liking and sensory characteristics (Dalenberg et al, 2014;. This guidance seems to be important with an eye on the increasing need for tailored and emotionally meaningful products for seniors (den Uijl, Jager, de Graaf, Waddell, & Kremer, 2014).…”
mentioning
confidence: 80%
“…pleasure-displeasure) and arousal (i.e. sleepiness-activation) (Dalenberg et al, 2014;, whereas for seniors few food-related results have been reported. Although seniors tend to rely more on their emotions and heuristics during various psychological processes, Svärd, Fischer, and Lundqvist (2014) have shown that older persons tend to report emotions with a lower level of valence and emotional arousal than their younger counterparts.…”
Section: Introductionmentioning
confidence: 93%